Princípio da proibição de retrocesso social: proteção de direitos fundamentais e análise crítica da jurisprudência do Supremo Tribunal Federal - Pedrotti, Leonardo de Faria Caminhoto (2023)
The dissertation analyzes the principle of prohibition of social regression, which, in the understanding of the Federal Supreme Court (STF), is implicit in the Federal Constitution of 1988. The principle, on the one hand, aims to prevent social achievements in terms of fundamental rights from being suppressed or reduced without compensatory measures, but, on the other hand, it cannot be interpreted in such a way as to impede legislative activity when regulatory adjustments, amendments and/or choices adopted are justified. The study is divided into five chapters. In the first three, the principle is based on legal-philosophical, historical and sociological terms, such as with international and national normative parameters, offering the context of the construction of the principle and its development, and relating it, as much as possible, with the understanding of Ministers of the STF on the subject. The fourth and fifth chapters of the study present a complete overview of the application of the principle by the STF, such as critics of this application, involving the 75 case law judged over 25 years. Case law are organized chronologically to narrate the development of the understanding of the STF; are presented quantitatively; and are also the object of critical analysis. The principle has application in the protection of fundamental rights as a whole and in the social achievements obtained by them – civil, political, social, economic, cultural, environmental, among others. And it will be applied, primarily, against the infra constitutional legislation that violates these achievements, so that the STF, when considering the principle was violated, prevents the normative act from producing its effects through the suspension of its effectiveness or, in definitive, through the declaration of its unconstitutionality. The understanding reached by the STF regarding the application of the principle of prohibition of social regression is the result of a long process of collegiate debate by the Court, which is profoundly studied in this work